2022
DOI: 10.3390/life12091387
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacological Potential of Novel Exopolysaccharide Isolated from Marine Kocuria sp. Strain AG5: Broad-Spectrum Biological Investigations

Abstract: With more than 17 clinically approved Drugs and over 20 prodrugs under clinical investigations, marine bacteria are believed to have a potential supply of innovative therapeutic bioactive compounds. In the current study, Kocuria sp. strain AG5 isolated from the Red Sea was identified and characterized by biochemical and physiological analysis, and examination of a phylogenetic 16S rRNA sequences. Innovative exopolysaccharide (EPS) was separated from the AG5 isolate as a major fraction of EPS (EPSR5, 6.84 g/L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…For example, Kocuria sp. has been reported to produce exopolysaccharides . Our team found that the fungal predominant bacteria Blastobotrys can produce EPS, and the EPS produced has a bile acid binding ability.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Kocuria sp. has been reported to produce exopolysaccharides . Our team found that the fungal predominant bacteria Blastobotrys can produce EPS, and the EPS produced has a bile acid binding ability.…”
Section: Discussionmentioning
confidence: 84%
“…has been reported to produce exopolysaccharides. 40 Our team found that the fungal predominant bacteria Blastobotrys can produce EPS, and the EPS produced has a bile acid binding ability. In conclusion, microorganisms play an important role in the degradation and transformation of polysaccharides in the cell wall of Liupao tea.…”
Section: Journal Of Agricultural Andmentioning
confidence: 95%
“…had a suppressive impact on the growth of cancer cells. 12 The highest IC 50s was (1691.00 ± 44.20 μg mL −1 ) for MCF-7, and the lowest was (453.46 ± 21.80 μg mL −1 ) for HepG-2. An exopolysaccharide from Bacillus albus DM-15 isolated from Indian Ayurvedic had an IC 50 value of 20 ± 0.97 μg mL −1 against lung cancer cell line (A549), and cellular staining showed necrotic, apoptotic properties in damaged A549 cells.…”
Section: Discussionmentioning
confidence: 89%
“…Following our findings, EPSR5, an acidic microbial exopolysaccharide extracted from marine Kocuria sp., its highest DPPH radical scavenging of 98% was recorded after 120 min at a concentration of 2000 μg/mL ( Alshawwa et al, 2022 ). Also, Another EPS isolated from B. subtilis AG4 exhibited 97.6% DPPH scavenging activity at 1500 μg/mL, IC 50 = 300 μg/mL, and 64.8% H 2 O 2 scavenging, IC 50 = 1,500 μg/mL at the same tested concentration ( Abdel-Wahab et al, 2022 )—another EPS from Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds exhibited promising therapeutic potential. For instance, they inhibit the proliferation of pathogenic bacteria and fungi ( Selim et al, 2022 ), impede the proliferation of malignant cells ( Abdel-Wahab et al, 2022 ), scavenge reactive oxygen species ( Alshawwa et al, 2022 ), diminish inflammation ( Alharbi et al, 2023 ), and expedite the process of wound repair ( Zaghloul and Ibrahim, 2022 ). These microbial bioactive metabolites encompass a diverse range of chemical structures, including peptides, lipopeptides, polypeptides, lactones, fatty acids, polyketides, isocoumarins, terpenoids, and exopolysaccharides ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%